Major diseases affecting rubber and its control measures adopted by small growers of Tellicherry taluk - Gangadharan O P (Department of Plantation Crops and Spices, College of Horticulture, 1992)
A survey was conducted to study the incidence of three major diseases of rubber ,namely abnormal leaf fall , pink and powdery mildew in tellicherry taluk of Kerala State. The clonal susceptibility, percentages of damage, control measures adopted by growers and its recovery from disease were evaluated. Out of the 100 units surveyed, abnormal leaf fall cccured in 88 holdings , pink in 84 units and powdery mildew in 91 units. Most of the units were inflected by more than one disease. In 67units the three were infected with all the three diseases. Among the incidence of three disease, powdery mildew incidence was maximum in the area surveyed . The farmers ability to detect the disease symptoms at early stages was very poor compared to the other two diseases. Maximum tolerance to abnormal leaf fall disease was noticed in RRII 105and GT1. Since the planting material was RRII 105 in majourity of cases, the leaf retention during monsoon was satisfactory even without prophylactic spraying. Hence the growers who have planted with RRII 105 were found to forgo the generally accepted practice of prophylactic spraying with copper fungicides before the onset of monsoon. Generally mild infection of leaf fall was found not to cause crop loss. If spraying is not done in one season, susceptible clones experience crop loss. If the benefit can cover the expenditures on plant protection , then spraying is advantageous. Prophylactic spraying was found necessary in Tellicherry taluk for all the clones protection, then spraying is advantageous . Prophylactic spraying was found necessary in Tellicherry taulk for all the clones except, RRII105 Maximum incidence of pink was noticed in RRII 105 and minimum in PB 235 among the four clones found in the surveyed area. Bordeaux paste was the common fungicide used for the control of pink disease. Only few growers knew the correct method of preparation and application of Bordeaux paste. Careless treatment of the infected part and improper disposal of the infected plant parts were found to provide large inoculum for the repeated infection of the disease. The growers failed to detect the disease at the initial stages or sufficiently early to carry out effective control measures. Use of Thiride may be popularized, since it was found more effective in rainy season. Growers are to be made aware of the early symptoms of the disease, so as to enable early detection. Demonstration classes with the help of visual aids would be of great use. Though powdery mildew disease was very common in the surveyed area, most of the growers were found ignorant about the disease and its control measures. Prophylactic dusting is to be insisted at the time of bud break especially in areas where the incidence of powdery mildew was observed in the previous years. Four to six rounds of dusting should be done when the disease is noticed to protect the tender fiushes fully. RRII 105 was found suspectible to powdery mildew infection. Due to leaf fall, extra weeding is also found necessary. No powdery mildew disease appears to be the most severe disease in Tellichery taulk. The protective measures against powdery mildew are not adopted by the small growers mainly for want of plant protection equipments and its availability in time and the difficulity in procuring sulphur dust. Disease tolerant clones may be planted in future . Monoclone planting may be discouraged , to regulate the maladies of epidemics in future. The need for an intensive extension education programme to create awareness among small growers about the disease and its timely control is evident from the present study.